METODE PENGECORAN LOST FOAM MENJAWAB TANTANGAN DUNIA INDUSTRI PENGECORAN LOGAM - Sutiyoko Sutiyoko (JURNAL FOUNDRY, 2011)
Lost foam casting is a method of metal casting using polystyrene foam pattern. The pattern is glued with gating system, coated and embedded in unbounded sand. The mold is vibrated and liquid metal is poured on the gating system. Polystyrene foam will escape and is relpaced with liquid metal. The lost foam casting has many advantages. This method is capable to product a complex-shape object that difficult in sand mold casting. The mold does not require cup, drag and cores to make holes in casting. This method suitable in production of prototype product. The sand can be reused directly because the sand without a binder. The lost foam casting also has disadvantages. Porosity is higher than sand casting because of gas that resulted in decomposition of poltstyrene foam. Unbounded sand can fall into the liquid metal. Quality of the casting with the lost foam casting method is influenced by many factors. Temperature and filling speed, density of polystyrene foam, time of mold vibration, thickness of coating, size of sand and level of vacuum. The mold will be more solid if it is vibrated for longer time. The casting surface will besmoother if use the smaller size of sand.